Clinical-experimental correlation of residual spinal deformation development under the condition of thoracolumbar fractures - Popsuishapka, Konstantin; Karpinsky, Mykhaylo; Popov, Andrey; Subbota, Igor; Teslenko, Sergii (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
Objective: determination of residual deformation and fixation of the spine in thoracolumbar burst fractures. Methods: the results of X-ray and CT examinations of 49 patients were analyzed, which were divided into 4 groups depending on the magnitude of kyphotic deformation: I (16 people) — from 0º to 12º, II (21) —from 12º to 21º, III (7) — from 21º up to 30º, IV (5) — more than 30º. In the experiment, 6 physical models were created: 1st — normal; 2nd — up to 50 % of the vertebral body and one adjacent intervertebral disc were destroyed; 3rd — 50 % of vertebral body destroyed, one adjacent intervertebral disc, posterior parts of vertebral body and roots of arches (incomplete with type A explosive fracture); 4th — 50 % of vertebral body, one adjacent intervertebral disc, posterior parts of vertebral body, pedicles, interspinous ligaments (type AB, AC); 5th — the whole body (100 %) and two adjacent discs (full burst fracture type A); 6th — 100 % of the vertebral body, discs, pedicles and ligaments (damages of the AC type). Results: it is established that the parameters of the experimental models can be compared with the clinical data. The possibility of subsequent development of the spinal deformation is associated with the morphology of the injury. With the help of the developed experimental model, the main regularities of development of kyphotic deformation in thoracolumbar burst fractures were determined. It is shown that the destruction of the vertebral body to 50 % results into the development of primary deformation, which does not progress with further loading. Damage to the posterior support of the spinal column leads to the progression of residual deformation to 10 %. Conclusions: the deformation of the spine occurs during the destruction of the vertebral body, immediately at the time of injury and depends on its intensity. In case of damage to the posterior parts of the spine, in the case of subsequent loading, the deformation progression is possible.